(untitled) (African Journal of Science, Technology and Social Sciences, 2022)
Rapid population growth has significantly contributed to inadequate sanitation facilities especially in slums. The inadequacy in sanitation facilities results to poor hygiene thus promote spread of sanitation-related diseases such as diarrhea. This study investigated sanitation management strategies for promotion of public hygiene in slums. Three slums in Meru Municipality ward, namely, Mjini, Shauri Yako, and Majengo were identified as the target population for the study. Mixed methods approach was adopted in sampling. Each slum was treated as a cluster. Data was collected from 79 heads of households within the clusters and 5 key informants from the Municipality ward who included a municipal manager, assistant chief, Public Health Officer, MEWASS director, and Caritas director. The heads of the households were proportionally selected randomly from the clusters as determined using Fisher’s formula. Qualitative data was collected from the key informants. Quantitative data was analyzed using the Statistical Package for Social Sciences (SPPS) version 25 to generate frequency tables while qualitative data was presented thematically. The findings showed poor sanitation and hygiene status of the slum dwellers due to the lack of good sanitation facilities that could enable them dispose their excreta effectively. The study showed that 86% of the slum population did not access adequate sanitation facilities where 5.1% used flying toilets and other 1.3% used bucket latrines. The correlation between comfortability of toilet users and the use of toilets with flies and odour was 0.351(P=0.000) thus comfortability to use sanitation facilities in the slums depended on the status of the toilets. The correlation between presence of caretakers for slum toilets and maintenance of toilets was 0.478 with a p-value of 0.000. The correlation between willingness to pay for sanitation services and the type of toilets provided was 0.094 (p=0.035). Presence of flush water and absence of flies in toilets registered a correlation coefficient of 0.350 (p=0.000). The study recommended consideration of better strategies to enhance better living conditions amongst the slum dwellers lacking access to adequate sanitation services. Further, the government need to put in place policies and regulations to ensure adequate water supply, sanitation and hygiene to the slum dwellers.